PARENTS’ KNOWLEDGE, ATTITUDE AND PERCEPTION ABOUT THE COMMONLY USED DRUGS AND THEIR ADVERSE DRUG REACTIONS IN CHILDREN - DR. JAYSHREE S. DAWANE; MRS. KANCHAN D, BOROLE; DR. VIJAYA A. PANDIT; DR. SONALI D. SALUNKHE (International Journal of Pharma and Bio Sciences, 2013)
Increasing incidence of adverse drug reactions (ADRs) because of inadvertent use of medicines in children is a matter of serious health concern. Children depend on their parents for medication. Study was planned to assess parents’ knowledge about commonly used drugs in children for minor ailments and their adverse drug reactions (ADRs). A cross sectional study, 200 Parents of children below 12 yrs from low socioeconomic group were included in study. We interviewed one of the parents involved in taking care of child. Standardized and validated questionnaire was used. 94 % caretakers were mothers.74 % respondents had no knowledge about medicines and 86.5% unaware about ADRs. Most of the irregularities observed in measuring dose, increasing duration, confusion in multiple drugs and storage of medicines. Low literacy has a major impact on patients’ ability to understand potential ADRs and correct dosing. Parents had inadequate knowledge and misconceptions about drug use.